Total Laparoscopic Hysterectomy: A Two-Year Experience in Apollo Hospitals Dhaka - Begum, Monowara; Zulfiqar, Nasrin; Yasmin, Fatema (Pulse, 2016)
Objective: Aim of our study is to analyze the surgical outcome of total laparoscopic hysterectomy (TLH) in our patient perspective of Apollo Hospitals Dhaka. Methods: This is a retrospective, observational study where we have reviewed demographic data, intraoperative and postoperative outcomes, and morbidity data on 100 women who underwent TLH between January 2011 and December 2012. Results: Total 100 patients were studied. Among them five patient required conversion to laparotomy due to presence of severe adhesion. The major and minor complication rates were 2% (bladder injury-2 cases) and 0% respectively. The average operating time was 148 ± 40 minutes and the mean length of hospital stay was 3±1 day. The average uterine size was 10 ± 4 weeks. In our cases operating time and duration of hospital stay were very similar with lower procedural complications to other published data elsewhere. Conclusion: We have observed that TLH is a safe and acceptable alternative procedure to standard hysterectomy from the patients perspective at Apollo Hospital Dhaka. Pulse Vol.8 January-December 2015 p.21-29